SMA-based adaptive tuned mass dampers: Analysis and comparison. (1st March 2023) - Manzoni, S.; Argentino, A.; Lucà, F.; Berardengo, M.; Vanali, M.
Abstract: Different types of adaptive tuned mass dampers have been recently proposed in the literature. One of the most promising approaches to make tuned mass dampers adaptive is the use of shape memory alloys. In this class of tuned mass dampers, different layouts have been proposed. This paper aims at comparing the two main layouts (wire-based and beam-based) in terms of adaptation capability, exerted force and electrical power consumption. To this purpose, the models of the two layouts are developed. These models minimise the number of required inputs, which basically are only related to device geometry, shape memory alloy characteristics, and vibration input. After an experimental validation, the models are employed for the mentioned comparisons between the two considered layouts. Highlights: Detailed models for adaptive tuned mass dampers based on shape memory alloys. Comparison between beam- and wire-based tuned mass dampers. Comparison in term of adaptation capability, exerted force and power consumption.